O tédio como disposição de humor fundamental de nosso ser-aí atual na fenomenologia de Martin Heidegger - Carvalho, Aurélio Augusto Costa (2023)
This work aims to approach the phenomenological investigation about boredom developed by Martin Heidegger in the winter course of 1929/1930 entitled The fundamental concepts of metaphysics. World — Finitude — Loneliness. Furthermore, a brief introduction to the phenomenological mode of investigation will be developed, as well as the characterization of boredom as an attunement, an existential structure of Dasein, thematized in Being and Time (1927). The steps of this investigation involve thematizing specific situations in which boredom manifests itself; the way that which is boring “causes” boredom; passing-the-time as the immediate reaction to boredom; the structural moments of being-left-empty and being-held-in-limbo as structural moments of boredom; the respective transformations of those structural moments into three forms of boredom; the temporal character of boredom in each of these forms; and, finally, boredom as a fundamental attunement of our current existence (Dasein).